Zakat Fitrah dan Tradisi Lebaran Idul Fitri Muslim Bugis Bone Sulawesi Selatan - A. Sarjan (State Institute of Islamic Studies (IAIN) Salatiga, 2010)
Zakat al-fitr (charity given at the end of the fasting in the Islamic holy month Ramadan) is one of the (of Islam) which must be fulfilled by Muslim. Although this commandment has been …